Production of essential oil coated polycapralactone scaffold with antibacterial properties - ULAĞ, SONGÜL (My University, 2023)
Wound dressings are designed in a structure that can provide suitable environmental conditions for the healing of the wound that has occurred on any part of the skin. It can form an artificial tissue scaffold for cells and provides hygienic conditions for cells1 . Wound dressing is used in the treatment of wounds formed after various injuries and surgical interventions. The dressing protects the wound, reducing the risk of infection and accelerating the healing process. The dressings fit snugly to the wound area, closing the wound, reducing the risk of infection, and supporting the healing of injured tissues, helping the formation of new cells. It is used in the treatment of various wounds such as wound dressing, burns, cuts, scratches, surgical wounds2 . Extrusion bioprinting is based on the principle of extruding or dispersing material to build a 3D structure layer by layer. Typical extrusion bioprinting systems use pneumatic, screw-based or pistonbased mechanisms. Pneumatic systems are preferred because of their simplicity, but printing characteristics are largely dependent on the viscosity of the material.3 Mechanical systems are attractive because of the precise control of material flow; however, these systems generate high pressure and can damage the cells contained in the bioink. Fine details of the dressing can be produced with 3D extrusion printers. This technology is a method that can be used to create precise and customized dressings. In this proposed study, the wound dressing will be produced using an extrusion 3D printer (Hyrel 3D). In the next step, the produced wound dressings will be covered with polylactic acid (PLA) microparticles loaded with photosensitive, electrical properties and photodynamic activity of cardamom oil and St. John's wort oil nanoparticle using the electro-hydrodynamic atomization method (EDHA), which allows to produce micron-sized particles. Characterization tests of this sensitized wound dressing will be performed. Electron microscope (SEM) will be used to view the morphology of the wound dressing, Fourier transform infrared (FTIR) spectrometer device to learn about its molecular structure, differential scanning calorimetry (DSC) device to detect its thermal properties, tensile device to detect tensile strength, swelling and degradation tests. It will be tested on S.aureus and P.acruginosa bacteria to determine its antimicrobial property. In vitro cytotoxicity will be tested by performing a cell culture study. As a result, the proposed study aims to use an antimicrobial wound dressing with a surface coated with microparticles.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)